'Prime Time of Life', A 12-Week Home-Based Online Multimodal Exercise Training and Health Education Programme for Middle-Aged and Older Adults in Laois. Issue 1 (2nd September 2021) - Cooper, Diane; Kavanagh, Ruth; Bolton, John; Myers, Caroline; O'Connor, Siobhán
Introduction: Multimodal exercise training can ameliorate the physiological decline associated with ageing. This study aimed to investigate whether 12 weeks of a home-based online multimodal training and health education intervention could improve functional ability and perceptions of physical and mental health in middle-aged and older adults. Methods: Sixty-one male (N = 18, 59.1 ± 7.0 years) and female (N = 43, 60.9 ± 6.8 years) participants with various clinical conditions completed two 60-minute training sessions per week for 12 weeks delivered online via Zoom. All sessions included aerobic, resistance, balance, and flexibility exercises. One weekly session incorporated 15 minutes of health and fitness education. The pre/post testing sessions were conducted in a local community centre in line with COVID-19 public health guidelines. Paired samples t-tests and the Wilcoxon signed rank tests were utilised to compare scores pre and post intervention. Results: There were significant improvements in participants 6-minute walk (p < 0.0001), sit-to-stand (p < 0.0001), timed-up-and-go (p < 0.0001), sit-and-reach (p < 0.0001), squat jump (p < 0.0001), core endurance (p < 0.0001), grip strength (right hand p = 0.03, left hand p = 0.04) and balance (right leg p < 0.0001, left leg p = 0.004) tests post intervention. Perceptions of physical (p < 0.0001) and mental (p < 0.0001) health also improved significantly. Discussion: Twelve weeks of online multimodal training and health education can significantly improve cardiovascular fitness, strength, power, balance, flexibility, and perceptions of physical health, mental health, and quality of life in middle-aged and older adults. While there are some limitations to online interventions, the benefits are numerous and equal to those reported for onsite interventions and should be considered for wider rollout in this population.